LOGAM KROMIUM (Cr) dan SENG (Zn) DALAM AKAR, BATANG, DAN DAUN TUMBUHAN MANGROVE Rhizophora apiculata DI MUARA SUNGAI BADUNG - Eka Suprihatin, Iryanti; Manurung, Manuntun; Mayangsari, Devi (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 2 Juli 2014, 2014)
Cr and Zn contents in the roots, trunks and leaves of the Rhizophora apiculata in estuary of Badung river have been investigated. This study was aimed to determine the ability of Rhizophora apiculata in accumulating heavy metals from the ecosystem. The concentrations of Cr and Zn in the water, sediments, roots, trunks and leaves were determined by the use of Atomic Absorption Spectrophotometer. The results showed that the highest concentrations of both Cr and Zn were found in leaves of the Rhizophora apiculata. Total Cr dan Zn concentrations in the roots were 2,49±0.19 and 19,4 ± 0,06 mg/kg respectively and in the trunks were 3,26 ± 0,28 and 4,14±0,32 mg/kg respectively, while in the leaves were 4,45 ±0,07 and 38,72 ±0,03 mg/kg respectively. The water and sediment contents of the metals were reported separately, and they were much lower than those in the plant samples. Upon comparing these values, it can be suggested that the Rhizophora apiculata was capable of accumulating heavy metals present in its environment.
Keywords: mangrove, Rhizophora apiculata, Cr and Zn metal